Density and Viscosity of Amino Acid Serine in Aqueous Dimethyl Sulfoxide Solution at Different Temperatures - AL-Dulaimy, Z.A.; AL-Amel, Z. W.; AL-Khalisy, R. S.; Hussein, Z. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Densities ï² and viscosity ï¨ of serine in 20, 40, and 60% (w/w) dimethyl sulfoxide (DMSO)-water mixtures were measured at 298.15, 303.15 and 308.15k. From these experimental data, apparent molal volume v ï¦ , limiting apparent molal volume v ï¦ o , the slop v S , transfer volume  v ï¦ o(tr), Jones-Dole coefficients A and B were calculated. The results are v ï¦ odiscussed the solute-solvent and solute-solute interaction, and showed that serine behaves as structure-breaker in aqueous DMSO solvent